A constituição do professor/pesquisador em contextos emergentes na educação superior - Zancan, Silvana (2018)
This thesis is linked to the Training, Knowledge and Professional Development Line of the Graduate Program in Education of the Universidade Federal de Santa Maria. The theoretical contributions of the Vygotski (1991, 2003, 2010), Bolzan (2002, 2005, 2006, 2009, 2010, 2014, 2016), Bolzan and Isaia (2006, 2009), Isaia and Bolzan (2007, 2009), Isaia (2002, 2006a, 2006b, 2009), Bolzan, Isaia and Maciel (2010), García (1998, 1999, 2009), Cunha (2004, 2005, 2012), Vaillant and Marcelo (2012), Freire (1996), Morosini (2001, 2006, 2009, 2013, 2014),Tardif (2002, 2011), Tardif and Gauthier (1996), Demo (2000, 2002, 2004), Pimenta and Anastasiou (2005) helped in the theoretical understanding of learning to be a professor / researcher in emerging contexts. We present the following question as a guiding problem of the study: how does the professor become a researcher in emerging contexts? Based on this concern, we defined the general objective of the research: to understand how the professor / researcher is constructed in the development of his/her activity in emerging contexts. As specific objectives: to identify the knowledge that the professor / researcher mobilizes to develop his / her research activities; recognize the emerging contexts in which professors / researchers are immersed; and identify the demands inherent to the research that the professor / researcher assumes. From this perspective, we opted for qualitative methodological approach based on sociocultural studies by Vygotski (1991, 2003, 2010), Bakhtin (2011), Connely and Clandinin (1995), Jovchelovitch and Bauer (2002), Bauer and Gaskell (2002), Freitas (2002), Freire (1987, 1996), Bolzan (2002, 2006), Bolzan and Isaia (2006), whose theoretical-methodological assumptions contributed to the analysis of the narratives by 09 professors / researchers, who work in the following Post-Graduation Programs of UFSM: Veterinary Medicine; Biological Sciences: Toxicological Biochemistry; Human Communication Disorders; Chemistry; Communication; Education; Administration; Electrical engineering; and Language. In the interpretation of the narratives, we explain the existence of a key category: learning to be a professor / researcher, which consists of 03 dimensions: training in and for research; professional experiences that imply research; and challenges and directions of research. These dimensions identified the transversal axis, an emergent context, that permeates through the actions and activities of the training of a professor / researcher. The study of these aspects allows defending that the learning of being a professor / researcher is an activity implied by challenges, tensions and demands that permeate the constitution of teaching, as the plural knowledge is mobilized and produce definitions and meanings to the field of action and research. We identified that learning to be a professor / researcher is a complex process, articulated and shared in all dimensions that develop teaching and research activities, from the emerging contexts that are immersed in the university. The relevance of this study implies the possibility of generating reflections about whether to produce professor / researcher in emergent contexts.